The correlation between motor proficiency and physical activity in Senior Phase learners in the Potchefstroom area - Lizl-Louise van Niekerk; Dorita du Toit; Anita E. Pienaar (AOSIS, 2016)
Background: One of the risks associated with low physical activity levels is the insufficient development of motor proficiency, which in turn has an impact on participation in physical activity and sport during adolescence. Objectives: To determine the relationship between motor proficiency and physical activity levels in adolescent Senior Phase learners in Potchefstroom, South Africa. No literature exists on the relationship between motor proficiency and physical activity levels among South African adolescents. Method: A total of 239 13- to 14-year-old learners were assessed using the Bruininkse Oseretsky Test of Motor Proficiency 2 (BOT-2) for motor proficiency, and the International Physical Activity Questionnaire (IPAQ) for physical activity levels. Data analysis included descriptive statistics, Spearman correlation coefficients and effect sizes. Results: Statistically and practically significant correlations were found between the total BOT-2 score and the physical activity levels of the total group, as well as the boys and the girls respectively. Fine motor coordination correlated with physical activity levels in the girls, while manipulation coordination correlated with the physical activity levels of the total group and the boys. The body coordination skill of jumping in place and the strength test items showed strong correlations with physical activity in all the groups. Conclusion: The motor skills of Senior Phase learners, especially coordination and strength skills, should be developed and maintained in the Physical Education curriculum to enhance physical activity levels.